SMART APPLICATION OF CLASS XI MATHEMATICS FORMULAS BASED ON ANDROID - Musa, Olha; Ali, Satriadi D; Badaruddin, Muliati (Jambura Journal of Electrical and Electronics Engineering, 2025)
Mastering mathematical formulas is often a challenge for high school students, especially grade XI students who cover complex topics such as algebra, trigonometry, calculus, and matrices. To help students understand and apply these formulas, an Android-based application was designed that provides interactive, easily accessible, and efficient learning facilities. Technological advances allow tasks to be completed more easily and in a shorter time, but increasingly sophisticated AI can still make mistakes in language translation, for example in chatgpt, the author's concern is that if there is an error in making mathematical formulas in completing the grade XI assignment, it will mislead students if they do not pay close attention and lack knowledge in completing the assignment. This study uses a descriptive method, which aims to describe or analyze the results without making broader generalizations. Application development follows the Prototype method, a widely used software development approach that allows for continuous interaction between developers and users, ensuring a clear understanding of system requirements and functionality. The results of the study include software testing using whitebox testing, which focuses on the internal structure and implementation of the application code. At this stage, the tester has complete knowledge of the system architecture and code. In addition, black-box testing is used for functional testing, where the behavior of a system is assessed by analyzing inputs and outputs. In black-box testing, the application is run, and data is entered to verify whether the output matches the expected results. This combination of testing methods ensures the robustness and functionality of the application in supporting 11th grade students with mathematical formulas.